KAJIAN EFEKTIVITAS PENGELOLAAN KOLABORATIF TAMAN NASIONAL KUTAI - Faiqotul Falah (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2013)
Kutai National Park (TNK) area has been defragmented and degraded due to illegal logging, forest fire, and land occupation. Collaborative management of TNK has been exists with the establishment of Mitra Kutai However various problems occur in TNK as indication that the collaborative management has not yet effective. This paper aims to describe information regarding the institutional effectiveness of collaborative management in TNK. This research was conducted by : 1) identification of related policies; 2) policy content analysis; 3) identific.ation of stakeholders' perception and roles, 4) qualitative analysis on stakeholders'perception and roles, 5) SWOT analysis, and 6) formulation of recommendation on improvement steps of collaborative management of TNK. It was concluded that collaborative management of TNK was ineffective in solving various problems occurred, and thereforeit is necessary to make improvement by the following steps: 1) Study the potential and current conditions of TNK; 2) Publish research results and raise issues on the problems and important values of TNK; 3) Streng then networking with funding organizations; 4) Establish zonation area; 5) Reconfigure collaboration management organization and arrange programmes and scheme on budget agreed by all stakeholders; 6) Make collaboration on the development of model of conservation village; and 7) Collaboration in the economic utilization programmes in TNK, such as development of agro-tourism area, the environmental education center, safari-park and eco-tourism areas and research area.